2004
DOI: 10.1089/gte.2004.8.407
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the C282Y, H63D, and S65C Mutations of theHFEGene in 1,146 Newborns from a Region of Northern Spain

Abstract: In Spain, 85% of patients with genetic hemochromatosis (GH) are homozygous for the C282Y mutation of the HFE gene. H63D and S65C mutations of HFE may also play some role in the disease. The aim of this study was to establish the prevalence of C282Y, H63D, and S65C mutations of the HFE gene in newborns in Catalonia, Spain. One thousand one hundred forty-six newborn screening cards were selected randomly. DNA from these cards was extracted and HFE mutations were analyzed with the LightCycler equipment (Roche Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…Finally, as regards the S65C mutation, although a low frequency was observed, this is higher than other reported Mediterranean populations (1).…”
Section: Distribution Of Genotypes and Alleles (C282y H63d And S65c contrasting
confidence: 65%
See 1 more Smart Citation
“…Finally, as regards the S65C mutation, although a low frequency was observed, this is higher than other reported Mediterranean populations (1).…”
Section: Distribution Of Genotypes and Alleles (C282y H63d And S65c contrasting
confidence: 65%
“…Two common mutations in the HFE gene account for the majority of the patients with HH. Another HFE mutation, S65C, was also implicated in the development of a mild form of HH (1).…”
Section: Distribution Of Genotypes and Alleles (C282y H63d And S65c mentioning
confidence: 99%
“…Transferrin saturation and serum ferritin were measured at diagnosis by standard methods in samples obtained after an overnight fast. In those patients with a transferrin saturation index ≥55% or a serum ferritin level ≥400 μg/L on two occasions, HFE mutations were analysed using the LightCycler® 2.0 Real-Time Polymerase Chain Reaction (PCR) System [2] (Roche Diagnostics Gmbh, Mannheim, Germany). One hundred non-related homozygous C282Y patients were finally included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Transferrin saturation and serum ferritin were measured at diagnosis by standard methods in samples obtained after an overnight fast. In those patients with a transferin saturation index ≥55% or a serum ferritin level ≥400 μg/l on two occasions, HFE mutations were analysed using the LightCycler equipment [3] (Roche Diagnostics Gmbh, Mannheim, Germany). Finally, 100 non-related homozygous C282Y patients were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Most HH patients (type 1 HH) are homozygous for a missense mutation (C282Y) in the gene HFE, located on 6p22.1, that disrupts the conformation of an atypical major histocompatibility class I molecule [12,18]. In Spain, 0.1% of people are homozygous for this mutation [3,27]. However, the penetrance of the disease in subjects with the YY genotype is not complete [2,7], and a number of studies have demonstrated high prevalence and low morbidity of type 1 hereditary haemochromatosis [1,5,28].…”
Section: Introductionmentioning
confidence: 99%